2020
DOI: 10.1177/0300985820932140
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Intestinal Innate Mucosal Immunity of Weaned Pigs During Porcine Epidemic Diarrhea Virus Infection

Abstract: In the small intestine, localized innate mucosal immunity is critical for intestinal homeostasis. Porcine epidemic diarrhea virus (PEDV) infection induces villus injury and impairs digestive function. Moreover, the infection might comprise localized innate mucosal immunity. This study investigated specific enterocyte subtypes and innate immune components of weaned pigs during PEDV infection. Four-week-old pigs were orally inoculated with PEDV IN19338 strain (n = 40) or sham-inoculated (n = 24). At day post ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…Interestingly, these post-infection alterations in villus tips were observed in jejunum but not in the ileum. Based on our previous study ( Chen et al, 2020 ), PEDV infection resulted in decreased VH:CD ratios in jejunum on DPI 2, 4, and 6 and in ileum on DPI 4 only, and the results indicate that jejunum had more severe villus injury than ileum. Moreover, in the present study, a positive correlation was observed between the E-cadherin expression and VH:CD ratio.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Interestingly, these post-infection alterations in villus tips were observed in jejunum but not in the ileum. Based on our previous study ( Chen et al, 2020 ), PEDV infection resulted in decreased VH:CD ratios in jejunum on DPI 2, 4, and 6 and in ileum on DPI 4 only, and the results indicate that jejunum had more severe villus injury than ileum. Moreover, in the present study, a positive correlation was observed between the E-cadherin expression and VH:CD ratio.…”
Section: Discussionmentioning
confidence: 65%
“…Fixed tissue procedures are described below. The clinical disease incidence, fecal virus shedding data, jejunum and ileum VH:CD ratios, and PEDV antigen detection by immunohistochemistry (IHC) at DPI 2, 4, 6 and 10 have been reported in a previous paper ( Chen et al, 2020 ). Pigs at DPI 10 were selected in the present study to assess intestinal restitution at the end of the study duration.…”
Section: Methodsmentioning
confidence: 92%
See 2 more Smart Citations
“…The clinical signs in PED virus (PEDV)-infected pigs are age-dependent, wherein younger pigs have higher morbidity and mortality [1]. In weaned pigs, PEDV affects their innate immunity through a decrease in Peyer's patch M cells and lysozyme expression in Paneth cells [2].…”
Section: Introductionmentioning
confidence: 99%